The Fund's Income Position for FY 2010-Midyear Review. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper updates the outlook for the Fund's income position for FY 2010, taking into account developments in the first half of the financial year. The FY 2010 income outlook has improved relative to the baseline projections at the beginning of the year,1 mainly as a result of the combination of higher projected lending income, and lower expenditures, in SDR terms, reflecting the depreciation of the U.S. dollar and a projected underrun in the budget. Net operational income for FY 2010 is projected at about SDR 440 million compared with the previous baseline projection of SDR 290 million in April 2009. However, the actual outcome is subject to considerable uncertainty related to the timing and amounts of disbursements under current and potential new arrangements and the performance of the Investment Account.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Cost; Interest Rate; Outturn; PP; Proceeds; United States